The Effect Of Different Curing Time on Giomer’s Fluoride Release - Raihan Zachary Ramadhan; Irfan Dwiandhono; Pratiwi Nur Widyaningsih (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2023)
Dental caries is one of the chronic disease of the oral cavity with a prevalence of 45,3% in indonesia. Fluoride is one of the substance that could help in preventing carries and secondary carries. Fluoride can also be found in restorative materials used in dentistry that could release fluoride ions inside the oral cavity. The aim of this study is to determine the differences of different curing time on giomer’s fluoride release.The method used in this study is experimental laboratory design using 27 giomer samples that are divided into 3 groups based on the duration of irradiation of 20 seconds, 40 seconds, and 60 seconds. Fluoride-release were observed by immersing the polymerized restorative material into artificial saliva and then tested using UV-Vis Spectrophotometer with a wavelength of 570 nm. One way ANOVA test showed differences in fluoride levels in the 3 treatment groups with p 0.05. There was a significant difference in fluoride levels between polymerized giomer restorative materials with curing time of 20, 40, and 60 seconds.